Visual perception strategies of foil fencers facing right- versus left-handed opponents - Witkowski, M; Tomczak, M.; Bronikowski, M.; Marciniak, M.; Borysiuk, Z. (Perceptual and Motor Skills, 2018)
This study sought to determine differences in fencers` visual perceptions during duels (preparatory actions) with right- versus left-handed opponents. Participants were 12 top-ranking right-handed female foil fencers (aged 16-30 years, M = 20.86, SD = 4.76) taking part in a training camp. Testing employed SensoMotoric Instruments Eye Tracking Glasses (SMI ETG 2.0) with eye-tracking analyses covering the visual attention time devoted to various areas of the opposing fencer`s body (areas of interest), average fixation, number of glances, and number of fixations during preparatory actions in duels. Each test was conducted during preparatory actions in 20-second staged duels, first against a right-handed, and then against a left-handed opponent. Against left-handed (vs. right-handed) opponents, fencers spent significantly more time looking at and significantly more often fixated on the armed hand. When fighting against right-handed (vs. left-handed) opponents, fencers devoted more time and fixated more often on the opponent`s upper torso. These results may point to an interesting phenomenon in which left-handed fencers benefit from weaker strategies adopted by their right-handed opponents who may fixate on the forearm and arm of the weapon hand.